Лучшие помощники
- Megamozg 2205 б
- Matalya1 1800 б
- DevAdmin 1720 б
- arkasha_bortnikov 895 б
- Dwayne_Johnson 860 б
3 апреля 2023 07:07
888
Упростите выражения
sqrt(3-2sqrt(2))+2-sqrt(2)
1
ответ
sqrt(3-2sqrt(2))+2-sqrt(2)=
sqrt(1-2sqrt(2)+2)+2-sqrt(2)=
sqrt((1-sqrt(2))^2)+2-sqrt(2)=
sqrt((sqrt(2)-1)^2)+2-sqrt(2)=
sqrt(2)-1+2-sqrt(2)=
1
sqrt(1-2sqrt(2)+2)+2-sqrt(2)=
sqrt((1-sqrt(2))^2)+2-sqrt(2)=
sqrt((sqrt(2)-1)^2)+2-sqrt(2)=
sqrt(2)-1+2-sqrt(2)=
1
0
·
Хороший ответ
5 апреля 2023 07:07
Остались вопросы?